Problems Faced by Indian Poultry Farm Exporters and Role of Exim Bank - Mohanraj, R.; Manivannan, L. (Prabandhan: Indian Journal of Management, 2010)
Poultry has a crucial place in India as the eggs and chicken meat are important and rich sources of protein, vitamins and minerals. Poultry provides rich organic manure and is an important source of income and employment to millions of farmers and other persons engaged in allied activities in the poultry industry. Exim Bank ( Export-Import Bank of India) is an Indian government-owned financial institution for the public sector created by and Act of the Parliament of India: the Export-Import Bank of India Act 1981. Exim Bank is managed by a Board of Directors, which has representatives from the Government, Reserve Bank of India, Export Credit Guarantee Corporation of India (ECGC), a financial institution, public sector banks, and the business community. India is the world’s fifth largest egg producing country. It also produces 530 million broilers per year. Poultry provides employment to about 1.5 million people. The annual per capita consumption in India is only 33 eggs and 630 grams of poultry meat. This is much lower as compared to the world average of 124 eggs and 5.9 kg meat. Indian companies acquire manufacturing units and distribution outlets in world markets. Remarkable feature of India’s exports was that they were driven by domestic companies. Only 10 per cent of India’s exports were by multinational corporations, while in the case of China, MNCs accounted for 52 per cent of exports.The National Committee on Human Nutrition in India has recommended per capita of 180 eggs (about one egg every two days) and 10.8 kg meat. To meet this target, it was estimated that 2010, the requirement will be 180 billion eggs and 9.1 billion kg poultry meat while the estimated production may only be around 46.2 billion eggs and 3.04 billion kg poultry meat. This shows that there is a tremendous scope for growth with rapid urbanization, and increasing demand from the present 250 million economically strong, consumer market base (which is likely to go up to 350 million by year 2010), there is bright future for this industry in India. It is estimated that, at present, Indian Poultry Industry contribution to the GDP is about ` 80 billion which is likely to reach ` 300 billion by the Year 2005.